Optimizing Ghanaian Postgraduate students’ job performance: The impact of polychronicity, work-school facilitation, and organisational support - Salomey Ofori Appiah; Richard Kofi Boateng (PLoS ONE, 2025)
This study examined the influence of polychronicity, work-school facilitation, and organizational support on the job performance of postgraduate students in Ghana. Guided by the Conservation of Resources (COR) theory, the research explored how personal and organizational resources affected job performance outcomes. A quantitative, explanatory research design was used. A sample of 341 distance education postgraduate students from three Ghanaian universities was selected using convenience sampling. Data were collected via a three-time lagged survey method to minimize common method bias. Structural Equation Modeling (SEM) using SMART PLS software (version 3.98) was employed for data analysis. The findings revealed that polychronicity had a significant positive effect on job performance. Organizational support moderated this relationship, strengthening the effect of polychronicity on job performance. Additionally, work-school facilitation mediated the relationship between polychronicity and job performance, suggesting that students who effectively balanced academic and work roles performed better. Polychronicity also directly influenced work-school facilitation. The study provided both theoretical and practical insights, highlighting the importance of individual time-use preferences and institutional support in enhancing the performance and well-being of postgraduate students.